2017
DOI: 10.15406/mojt.2017.03.00055
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Endosulfan on Acetylcholinesterase and Cellulase Enzyme Activity of Earthworm Eisenia Foetida

Abstract: Pesticides produces considerable effects on biochemical parameters of organisms and since enzymes allow specific reactions to proceed and collectively constitute the metabolism, studies on metabolic enzymes and proteins of earthworms may be useful biomarkers for ecotoxicological aspects. Endosulfan, belonging to the organochlorine group of pesticides on growth, reproduction and avoidance behavior of earthworm E. foetida and found that the pesticide significantly affected the parameters. Due to its used against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In two separate investigations, Earthworm (Eisenia fetida) showed avoidance responses to exposed Dimethoate and Dichlorvos pesticides. [44,45] The results of the present study showed that the pituitary thyroid axis was impacted, as re ected by the decrease in thyroid hormones (T3 and T4) and an increase of TSH after 14 d exposure of earthworm to acetamiprid. The decrease of T3 and T4 could be due to a reduction in their synthesis and release of these hormones and their storage in the colloids due to hypothyroidism.…”
Section: Discussionmentioning
confidence: 55%
“…In two separate investigations, Earthworm (Eisenia fetida) showed avoidance responses to exposed Dimethoate and Dichlorvos pesticides. [44,45] The results of the present study showed that the pituitary thyroid axis was impacted, as re ected by the decrease in thyroid hormones (T3 and T4) and an increase of TSH after 14 d exposure of earthworm to acetamiprid. The decrease of T3 and T4 could be due to a reduction in their synthesis and release of these hormones and their storage in the colloids due to hypothyroidism.…”
Section: Discussionmentioning
confidence: 55%